A novel bifunctional anti-PD-L1/TGF-β Trap fusion protein (M7824) efficiently reverts mesenchymalization of human lung cancer cells - Justin M. David; Charli Dominguez; Kristen K. McCampbell; James L. Gulley; Jeffrey Schlom; Claudia Palena (OncoImmunology, 2017)
Mesenchymalization is a cellular and molecular program in which epithelial cells progressively lose their well-differentiated phenotype and adopt mesenchymal characteristics. Tumor mesenchymalization occurs during the progression of cancer to metastatic disease, and is also associated with resistance to multiple therapeutics, including killing by cytotoxic immune cells. Furthermore, tumor cells can evade immune destruction by upregulating the checkpoint molecule PD-L1, and emerging research has found higher PD-L1 expression in mesenchymalized tumors. Here, the association between TGF-β1-mediated mesenchymalization and PD-L1 was investigated in non-small cell lung cancer cells (NSCLC). TGF-β1 was found to upregulate PD-L1 gene transcription in a Smad2-dependent manner, and a positive association between PD-L1 and phosphorylated Smad2 was found in NSCLC tumors. The potential to target these 2 negative immune regulators with a single agent was investigated using M7824, a novel clinical-stage bifunctional agent that targets both PD-L1 and TGF-β. Treatment of NSCLC cells with M7824 in vitro and in vivo attenuated features of TGF-β1-mediated mesenchymalization, including mesenchymal marker expression, proliferation suppression, and chemoresistance. These findings demonstrate that upregulation of tumor cell PD-L1 is a novel mechanism of TGF-β1-induced immunosuppression in NSCLC, and that treatment with M7824 has the potential to simultaneously block both tumor mesenchymalization and PD-L1-dependent immunosuppression.